Problematyka polskiej leksyki ogólnej w świetle Nisbettowskiej koncepcji geograficzno-kulturowych uwarunkowań myślenia - Rudnicka, Ewa (Investigationes Linguisticae, 2013)
The article deals with Nisbett’s conception of geography of thought and its linguistic confirmations. Basing on Nisbett’s theses the problem of Polish mentality and language is concerned. That is why lexis and some others linguistic aspects are analysed in purpose to find the answer for the question if Polish thought is more like Asian or more like Western. The main focus for research is the grammatical structure of Polish lexis, the percentage of polysemous words in Polish language and the generic usage of Polish nouns.